IS THERE AN ASSOCIATION BETWEEN AFFECTIVE TEMPERAMENT AND MORBID OBESITY IN CANDIDATES FOR BARIATRIC SURGERY? - Mousfi, Alexandre Karam Joaquim (2023)
Introduction: Numerous studies have demonstrated a strong relationship between obesity and psychiatric diseases, especially mood disorders. However, few have evaluated the correlation between morbid obesity and affective temperament. Objective: To study the existence of affective temperament in morbidly obese individuals before surgical treatment of obesity. Methods: The material for reading and analysis was selected from research on virtual platforms focusing on affective temperaments (hyperthymia, dysthymia and cyclothymia). A search was carried out for descriptors related to the topic ("temperament, morbid obesity, bariatric surgery, mood disorders” and their equivalents in English with AND or OR search), considering the title and/or abstract, and then reading the work in full. Results: The most common psychiatric comorbidities in overweight and obesity were mood, anxiety and binge eating disorders. The estimated prevalence of affective temperaments in morbidly obese people is about 65%. Conclusion: The prevalence of affective temperaments is higher in morbidly obese people, candidates for bariatric surgery, compared to the general population. Cyclothymic temperament is the most common in the morbidly obese patient population.